Compassion Training Alters Altruism and Neural Responses to Suffering - Weng, Helen Y.; Fox, Andrew S.; Shackman, Alexander J.; Stodola, Diane E.; Caldwell, Jessica Z. K.; Olson, Matthew C.; Rogers, Gregory M.; Davidson, Richard J. (Psychological Science, 2013)
Compassion is a key motivator of altruistic behavior, but little is known about individuals’ capacity to cultivate compassion through training. We examined whether compassion may be systematically trained by testing whether (a) short-term compassion training increases altruistic behavior and (b) individual differences in altruism are associated with training-induced changes in neural responses to suffering. In healthy adults, we found that compassion training increased altruistic redistribution of funds to a victim encountered outside of the training context. Furthermore, increased altruistic behavior after compassion training was associated with altered activation in brain regions implicated in social cognition and emotion regulation, including the inferior parietal cortex and dorsolateral prefrontal cortex (DLPFC), and in DLPFC connectivity with the nucleus accumbens. These results suggest that compassion can be cultivated with training and that greater altruistic behavior may emerge from increased engagement of neural systems implicated in understanding the suffering of other people, executive and emotional control, and reward processing.